KEMAMPUAN MEMBACA AL-QUR’AN MAHASISWA FAKULTAS USHULUDDIN UIN SYARIF HIDAYATULLAH JAKARTA ANGKATAN 2016/2017 - Dasrizal Dasrizal (Ushuluna: Jurnal Ilmu Ushuluddin, 2016)
The purpose of this study is to know the proficiency level of Faculty of Ushuluddin students in reciting the Qur’an and to know. The quantitative method was chosen as a method of study by involving 150 students. The data was found by using questionnaire and test analyzed using descriptive statistics [percentage, mean and standard deviation] and inferential statistics [t-test] using SPSS version 21.0. In general, the study has discovered that the proficiency level of students is moderate with mean 77,39. The inferential statistics of the hypothesis shows that there is a significant difference in proficiency level in reciting the Qur’an between male and female student, and there is no significant difference of proficiency level in reciting the Qur’an between the graduate students of Islamic high school and graduate students of high school. At the end of the research, the researcher presenting evaluation of the whole research and suggestions to improve competence of students in reciting of the Qur’an.